Lithium-ion batteries hazard and use assessment - Mikolajczak, Celina; Kahn, Michael; White, Kevin; Long, Richard Thomas; SpringerLink (Online service). (New York Springer, 2011)
Suitable for practitioners, this book examines the usage of lithium-ion batteries and cells within consumer, industrial and transportation products, and analyzes the potential hazards associated with their prolonged use. It also surveys the applicable codes and standards for lithium-ion technology
Introduction to Lithium-Ion Cells and Batteries -- Lithium-Ion Technology Applications -- Summary of Applicable Codes and Standards -- Lithium-Ion Battery Failures -- Life Cycles of Lithium-Ion Cells -- Lithium-Ion Fire Hazard Assessment -- Lithium-Ion Fire Hazard Gap Analysis -- Appendix A: Limitations
Includes bibliographical references
Electronic reproduction.
Keywords: Lithium ion batteries; Lithium ion batteries -- Safety measures; Lithium ion batteries -- Risk assessment